Synergistic interaction of 2-amino 4-methyl benzothiazole (AMBT) and benzotriazole (BTZ) offers excellent protection to mild steel exposed in acid atmosphere at elevated temperatures: Electrochemical, computational and surface studies - K.M. Shainy; Anupama R. Prasad; Asha Thomas; Abraham Joseph (Egyptian Journal of Petroleum)
The synergistic interactions and corrosion protection properties of 2-amino 4-methyl benzothiazole, (AMBT) and 1, 2, 3-benzotriazole (BTZ) have been studied for mild steel in HCl at elevated temperatures. The extent of synergistic interaction increases with temperature. The methods of study include the conventional weight loss studies, computational screening, surface characterization and electrochemical studies. Quantum chemical approach was used to calculate some electronic properties of the molecules and to ascertain the synergistic interaction, inhibitive effect and molecular structures. The corrosion inhibition efficiencies and the global chemical reactivity relate to parameters like total energy, EHOMO, ELUMO and gap energy (ΔE). Condensed atom Fukui functions also calculated using DFT at B3LYP/6-31G* level, and were found to be correlating with the experimental results. Keywords: Mild steel, AMBT, BTZ, Weight loss, EIS, Polarization